Teaching and Develop Pronounciation Using Media Podcast in Senior High School - Mutia Salma Rosa; Hilma Fitriana; Rifda Zulfiana (Lingua, 2020)
A wide range of English teaching and learning approaches have emerged due to information and communication technology advancement. According to Constantine (2007), Podcast was first known in 2004, and it is defined as an internet audio blogging or internet audio publishing. Research on podcasting pedagogy suggests that podcasting helps learners boost their English language skills and support areas such as grammar, pronunciation, and vocabulary. The results of the research consist of 180 students of grade eleven at SMA 1 MAJA and consisting of 6 classes. To determine the sample of this research, the writer used Cluster Random Sampling. The result of the highest score of the pre-test was 75 and the post-test was 90. Learning through podcasts as a learning tool that can attract students' attention and provide information, knowledge and enrich vocabulary.